Pengaruh Fasilitas Belajar dan Lingkungan Keluarga Terhadap Motivasi Belajar Sains Peserta Didik Kelas V Sekolah Dasar - Zebua, Roman Sartika; Zega, Nofridayasari; Hulu, Trysna Febryani; Zai, Ratna Febriani; Harefa, Oberius Jaya; Gea, Revisi; Lase, Ridho Krisman; Gea, Revisman; Harefa, Edward (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to analyze the relationship betwen learning facilities and the family environment on student science learning motivation. The background to this research is based on the importance of these two factors in supporting the learning process. Adequate learning facilities, such as book, teaching aids and accsess to thecnology, are expected to increase student interest and motivation in learning science. Apart from that, a supportive family environment, such as good communication between parents and children and encouragement to learn, also contributes to student learning motivation. The data collection method used in this research in quantitative data, which allows researchers to find out how strong the relationship is between the variabels of learning facilities and family environment and learning motivation. Data was collected throught questionnaires distributed to student at school. The result of the analysis shows that there is a significant positive relationship between learning facilities and the family environment on science learning motivation, which means that the better the facilities and family support, the higher the students learning motivation. It is hoped that this reseach will provide insigh for educators and parents regarding the importance of creating a supportive learning environment to increase student learning motivation in the field of science